2003
DOI: 10.1530/eje.0.1480497
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid consequences of the Chernobyl nuclear power station accident on the Turkish population

Abstract: Objective: The Chernobyl accident caused widespread effects across Europe and huge areas were radiocontaminated. The major impact of the accident on human health was a sharp increase in childhood thyroid carcinoma and autoimmune thyroid diseases in exposed populations. The thyroidal effects of the Chernobyl accident have been investigated in most European countries, except Turkey. The aim of the current study was therefore to determine the thyroidal consequences of the Chernobyl nuclear power station accident … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2006
2006
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 38 publications
0
7
0
Order By: Relevance
“…In 2003, Emral et al [24] undertook a two-zone study in children who were aged under 5 years at the time of the Chernobyl accident and were living in the eastern Black Sea and inner Anatolia regions. This study pointed out that there was a slight increase in nodule prevalence and thyroid antibody-positive subjects in the Black Sea region.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In 2003, Emral et al [24] undertook a two-zone study in children who were aged under 5 years at the time of the Chernobyl accident and were living in the eastern Black Sea and inner Anatolia regions. This study pointed out that there was a slight increase in nodule prevalence and thyroid antibody-positive subjects in the Black Sea region.…”
Section: Discussionmentioning
confidence: 99%
“…As of 1999, mandatory iodization of household salt has been put into effect in Turkey. Three years after this policy, iodine-deficient regions became iodine-sufficient areas [24]. It is known that both iodine deficiency and iodine excess have a triggering effect in thyroid malignancies, especially with regard to papillary microcarcinoma in the case of mandatory iodization [25,26].…”
Section: Discussionmentioning
confidence: 99%
“…For the determination of goiter, World Health Organization and International Council for Control of Iodine Deficiency Disorders criteria were used. Thyroid volume over 13.9 ml in boys and 14.6 ml in girls for 14-year old adolescents and thyroid volumes over 16.0 ml in boys and 16.1 ml in girls for 15-to 18-year old adolescents were accepted as goiter (18,19).…”
Section: Laboratory Methodsmentioning
confidence: 99%
“…In contrast, Drozd et al [23] reported that among 1,132 highly irradiated children (4–14 years old when exposed and 8–18 when investigated), the proportion of TN patients and the proportion of TC among TN patients were 1.2% and 50%, respectively, much higher than in the control unexposed population where a few benign nodules and no cancer were observed. In 2 studies, each comparing relatively contaminated areas far from Chernobyl, with a control group in more distant uncontaminated areas, no difference was found in children or adolescents, with a ratio of TN subjects/investigated subjects varying from 2% to 6% [24], [25]. Among children and adolescents exposed (0.79 grays) to 131 I after Chernobyl and evaluated 12 to 14 years later, TN was found in 2.7%, with 12% harboring TC [26].…”
Section: Discussionmentioning
confidence: 95%